WHAT IS THE PUTIN DOCTRINE? THE RUSSIAN STRATEGIC ISSUE AND ENLARGED NATIONAL SECURITY - Hage, José Alexandre Altahyde (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
The objective of this essay is to analyse the paper called Putin Doctrine, published by Sergei Karaganov, in January 2022, its relation with Russian expansionism found in the annexation of Ukrainian region of Crimeia, in 2014, and its criticism on emerging international system with the end of Cold War; it is an time considered quite harmful for the Russians and to power restoration of this country and its rise such as great power. The research covers the período between 1991, the end of the Soviet Union, and in January 2022, beginning of the Russian-Ukrainian hostilities over Donbass. The argumentative line, theoretical-methodological of this paper uses the literature of the geopolitics and realist thinkers belong to international relations school.